MINAT PEMUDA TANI TERHADAP TRANSFORMASI SEKTOR PERTANIAN DI KABUPATEN PONOROGO - Eri Yusnita Arvianti; Asnah Asnah; Anung Prasetyo (Universitas Tribhuwana Tunggadewi, 2015)
Youth of the nation in achieving milestones of development of a region Phenomenon among youth is often the case in rural areas. In Ponorogo society showed that in fact a large number of the population worked as agricultural labor switched professions to other sectors. Youth interest in trying peasant farmers are sometimes beaten by their interest to go abroad to look for a better job. This study aims to determine the factors that lead to low interest farm youth in the agricultural sector in Ponorogo from April to August 2015. The research was conducted in six villages, namely: Myrtle village, Mojorejo village, Siwalan village, Sukosari village, Demangan village, and Badegan village, based on the consideration that the location of the farm is still widespread, people do more overseas because earnings as a laborer was minimal. The method used is quantitative method. Each sample using a proportional stratified random sampling, the population is divided into several sections (subpopulations) in each district based on the number of workers employed in agriculture. Samples were taken 72 people. Analysis of data using multiple linear regression with SPSS. The results showed that income, condition family, community, and social significantly affect the interest of farmers and most respondents still have to to farm activity